GERMINATION AND SANITARY QUALITY OF SEEDS OF DEDALEIRO (Lafoensia pacari St. Hil., Lythraceae) - SENEME, Adriana Martinelli; HOFFMAN, Susane; POSSAMAI, Edilberto; MORAES, Carla Pedroso de (Scientia Agraria, 2010)
The present work had for objective to evaluate substrata and temperatures for the germination, to verify the effect of the storage in the physiologic quality and to evaluate the sanity of seeds Lafoensia pacari (St. Hil.). Was determined, in seeds collected in Curitiba (junho/2003): - moisture content (105 °C + 3 °C / 24 h); - germination: under temperatures of 20 °C and 30 °C, in substrata filter paper, vermiculite; thick sands; mixture of substrata (thick sands + vermiculite) and fine sands; evaluation to the 35 days after installation; - emergency in fine sand at green house. After the determinations the seeds were conditioned in paper sacks and stored in two ambient: laboratory and camera (T = 20 °C). To the 12 months, was determined the moisture content and germination being used the same substrata and temperature of 20 °C. First counting of germination (15 days), determination of the weight of dry matter of the normal seedlings (to the 30 days) and sanity test (“Blotter test”) in paper-filter (T = 22-25 °C). The statistical analysis after collection was in a complete randomized design and after storage an factorial 2 x 5 was used (storage and substrata); in both experiments six repetitions of 30 seeds were used for each treatment and the mean comparison with Tukey test (P>0,05). The best conditions for the germination are temperature of 20 °C and sands substratum; the storage in camera contributes to the maintenance of the germination of the seeds and that the fungus found in seeds were: Aspergillus niger, Fusarium semitectum e Penicilium sp.